Pengembangan Media Pembelajaran Digital Berbasis Scratch, Canva dan CapCut pada Materi Perubahan Energi - Khairunnisa Mardiyah; Jelita Jelita; Nuraida (CAHAYA: Journal of Research on Science Education, 2026)
This study aimed to develop and evaluate an integrated digital learning medium using Scratch, Canva, and CapCut for teaching energy transformation in IPAS to fourth-grade students at SD Negeri 1 Seulalah. The novelty of this study lies in the integration of three digital applications into a single learning medium to provide interactive, vusual, and engaging learning experiences for elementary school students. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 23 fourth-grade students and three validators, comprising a media expert, a material expert, and a language expert. Data were collected through observation, interviews, questionnaires, documentation, and pretest-posttest assessments. The results indicated that the developed learning medium was valid, practical, and effective for IPAS learning. Student responses reached 86%, categorized as very attractive, furthermore, students’ learning outcomes improved significantly, as reflected by an N-Gain score of 0,79, which falls with in the high category. These findings demonstrate that the integration of Scratch, Canva, and CapCut can enhance student engagement, facilitate conceptual understanding, and improve learning outcomes in energy transformation topics. In conclusion, the developed digital learning medium is feasible and effective for supporting IPAS learning in elementary schools and has the potential to promote more interactive and meaningful learning experiences.